NOSTALGIC PRODUCT DESIGN BASED ON HOMESICKNESS ELEMENTS IN TUPING VILLAGE - Shahriman Zainal Abidin,; Zhao Xuechun,; Mao Panyun,; S'harin Mokhtar, (Journal of Islamic, Social, Economics and Development, 2024)
Purpose: In the face of the inheritance of rural traditional culture and the sustainable development of rural society, through the product design of homesickness elements, let people understand the countryside, miss the countryside, and build the countryside. Methods: Based on the principles of green design and cultural regeneration, select representative homesickness elements to carry out nostalgic product design. Conclusion: The nostalgic product design of homesickness elements in Tuping Village has better stimulated people's love for the countryside, yearning for the harmonious co-existence of man and nature, and also attracted people's confidence in rebuilding the countryside and the consciousness of protecting the traditional rural culture.